Identification of Bacteria on Classroom Air Conditioner at Faculty of Medicine, Universitas Swadaya Gunung Jati, Cirebon, Indonesia - Surfa, Muhammad Bintang Abdi; Fitriani, Hikmah; Indrakusuma, Mohammad Erwin (GHMJ (Global Health Management Journal), 2024)
Background: Air conditioner became a significant factor in indoor air quality. Poorly maintained Air Conditioners can become breeding grounds for bacteria, leading to health problems and symptoms of Sick Building Syndrome, such as headaches, loss of concentration, dry throat, eye and skin irritation, and acute respiratory infections. Aims: Identify bacteria types and count bacterial colonies on Air Conditioning units in the classrooms of buildings A and B at Faculty of Medicine, Universitas Swadaya Gunung Jati, Cirebon, Indonesia. Methods: Cross-sectional study using 16 air conditioner samples from lecture rooms at Faculty of Medicine, Universitas Swadaya Gunung Jati. Direct swabs were taken from the air conditioner filters using cotton swabs, which were then identified using McConkey, Blood Agar, and Nutrient Agar media to count bacterial colonies followed by confirmatory bacterial tests using Triple Sugar Iron Agar (TSIA) and Indol, Methyl red, Vogues proskauer, Simmon Citrate (IMVIC) media. Results: Bacterial growth identification tests identified Bacillus sp., Micrococcus sp., Staphylococcus sp., Streptococcus sp., Coryneform/Diptheroid, Enterobacter sp., and Stenotrophomonas sp.. Highest colony count was 402 CFU/cm³ and lowest was 16 CFU/cm³. Conclusion: Bacterial identification on classroom the Air Conditioner revealed that the microbial community in the system was predominantly composed of Gram-positive strains, which were detected more frequently than Gram-negative strains. Received: 24 September 2024  |  Reviewed: 02 November 2024  |  Revised: 30 November 2024  |  Accepted: 15 December 2024.